Principles of Environmental Responsibility and the Construction of the Ricoti Highway - Khositashvili , Mzia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
Global warming and the resultant floods, landslides, and other natural disasters increasingly threaten the modern world. Additionally, the activities of numerous large and small organizations directly and indirectly affect the natural environment through waste generation, air and water pollution, depletion of natural resources, and infrastructural development. The impact on the environment is particularly evident in urban development and the construction of roads and highways. In recent years, Georgia has initiated several large-scale highway construction projects. Since gaining independence, Georgia has become a crucial transit country for domestic and foreign cargo transportation, prompting the modernization of the East-West highway. Highway construction can significantly alter the surrounding landscape, contributing to biodiversity loss and habitat degradation, thereby impacting the social and economic conditions of local residents. The article underscores the adverse environmental effects of highway construction and reconstruction, emphasizing the importance of adhering to principles of environmental responsibility by countries and organizations undertaking such projects. This entails implementing preventive measures, managing environmental risks, and conducting thorough environmental impact assessments. Notably, Georgia adheres to international declarations, standards, and agreements governing highway design and construction, ensuring the quality and safety of projects like the Ricoti road. Prior to constructing the Ricoti Highway, thorough assessments were conducted to anticipate potential negative environmental impacts. Mitigation measures were developed to minimize interference with natural landscapes, protect unstable ground structures, and mitigate impacts on vegetation, fauna, and the socio-economic environment. The article evaluates the adequacy of environmental protection measures outlined in the project and assesses efforts made to mitigate adverse environmental impacts.